SOSIALISASI DAN PEMBERIAN MINUMAN HERBAL JAHE SEBAGAI PENURUNAN TEKANAN DARAH DI POSYANDU LANSIA DESA ARA CONDONG DUSUN 7 WONOGIRI KABUPATEN LANGKAT - Gultom, Evi Deviana (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
Hypertension is one of the most common cardiovascular diseases suffered by the community. Hypertension is now a major problem for all of us, not only in Indonesia but in the world, because if it is not controlled properly it can be a risk factor for the emergence of complications such as heart, kidney failure, diabetes, stroke, retinopathy, nervous disorders and cerebral disorders. The increase in cases of hypertension can be caused by many factors, one of which is public knowledge that is not limited to hypertension, but what efforts can be made by the community to prevent and lower blood pressure. One of the efforts to increase people's knowledge is through counseling methods so that they are able to adopt a healthy lifestyle to improve their health. The purpose of this article is to obtain an overview of public knowledge about hypertension and to introduce herbal drinks from ginger that can lower blood pressure. The method was carried out with interactive counseling which was carried out at the Children's Poling Village Hall, Ara Condong village Langkat district, Dairi Regency using leaflet media, , and giving ginger drinks. The counseling was carried out smoothly and gave good results, where many people asked questions about their hypertension, how to avoid increasing blood pressure and trying to understand how to make the given ginger drink.